Preoperative Lignocaine Nebulization for Attenuation of the Pressor Response of Laryngoscopy and Tracheal Intubation in Patients Undergoing Laparoscopic Cholecystectomy Under General Anesthesia - Shakya, Shailendra; Shakya, Anuka; Paudel, Bibek (Journal of Nepalgunj Medical College, 2025)
Introduction: Laryngoscopy and intubation during laparoscopic cholecystectomy under general anesthesia can cause a pressor response, resulting in hemodynamic instability. Preoperative lignocaine nebulization provides topical anesthesia by inhibiting sodium channels and may offer better mucosal coverage than intravenous administration.Aims: To assess the effect of lignocaine nebulization on pressor response, hemodynamic stability, and related complications.Methods: This double-blinded comparative study was conducted from August to December 2024, involving 100 patients undergoing elective surgery under general anesthesia with physical status score I or II (American Society of Anesthesiologists). Patients were randomized into two groups for nebulization: Group A (n=50) received 2% lignocaine (3 mg/kg, volume adjusted with saline), while Group B (n=50) received an equivalent volume of 0.9% normal saline. Parameters analyzed included age, gender, weight, ASA physical status, SpO2, heart rate and mean arterial pressure. Statistical analysis was performed using Student’s t-test and Chi-square test; p